2013
DOI: 10.1038/bjc.2012.577
|View full text |Cite
|
Sign up to set email alerts
|

Male breast cancer, age and sex chromosome aneuploidy

Abstract: Background:In cultured, dividing transformed T lymphocytes and in dividing bone marrow cells from normal men and those with a haematological malignancy, sex chromosome aneuploidy has been found to increase in prevalence and degree with age. This has rarely been investigated in non-dividing uncultured blood samples. The loss and gain of the X chromosome in dividing transformed lymphocytes in women with age is much more frequent than that of the Y chromosome in males. However, paradoxically X chromosome aneuploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
2
11
0
1
Order By: Relevance
“…The data here shown are consistent with those presented by Jacobs et al [18] who demonstrated that sex chromosome aneuploidy in non-dividing nuclei of peripheral blood cells occurs frequently in adult men and increases with age. The data presented by Jacobs et al 18] did not completely clarify the relation between sex chromosome aneuploidy and occurrence of MBC, but suggested a possible role in favouring the neoplastic transformation.…”
Section: Accepted M Manuscriptsupporting
confidence: 93%
“…The data here shown are consistent with those presented by Jacobs et al [18] who demonstrated that sex chromosome aneuploidy in non-dividing nuclei of peripheral blood cells occurs frequently in adult men and increases with age. The data presented by Jacobs et al 18] did not completely clarify the relation between sex chromosome aneuploidy and occurrence of MBC, but suggested a possible role in favouring the neoplastic transformation.…”
Section: Accepted M Manuscriptsupporting
confidence: 93%
“…Since age and genomic instability are associated with failure of DNA repair and accumulation of DNA damage in the genome, many authors have evaluated the association between SCE frequency and age, but data in the literature are controversial (4,14,19,(22)(23)(24). In accordance with other studies, we found no correlation between age and SCE frequency, either in familial or in sporadic patients (4,14).…”
Section: Familial N=22supporting
confidence: 85%
“…Loss of Y-chromosome (LOY) has previously been described in several solid tumors, including esophageal carcinoma, pancreatic cancer, urothelial bladder cancer, colorectal cancer, and prostate cancer [6][7][8][9][10][11]. Early case reports described the presence of LOY in male BC tissue [10][11][12]. A larger, more recent study reported LOY in 5 out of 31 patients with male BC.…”
Section: Introductionmentioning
confidence: 99%